2022
DOI: 10.1200/jco.22.00491
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy or Autologous Stem-Cell Transplantation for Primary CNS Lymphoma in Patients Age 60 Years and Younger: Long-Term Results of the Randomized Phase II PRECIS Study

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. We previously reported the results of a randomized phase II study in patients with newly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 10 publications
5
34
0
Order By: Relevance
“…Long-term follow-up of randomized phase 2 PRECIS study demonstrated advantage in 8-y event-free survival in ASCT arm over WBRT with 40 Gy (67% and 39%, respectively, p = 0.03), but without OS benefit (69% and 65%, respectively). Conversely, a significant deterioration in balances (52% vs. 10%, P ≤ 0.001) and neurocognition (64% vs. 13%, P < .001) was observed in WBRT over ASCT arm, suggesting avoidance of 40 Gy WBRT in consolidation within the first line treatment [35]. A systematic review and meta-analysis of 13 prospective trials encompassing 348 PCNSL patients treated with ASCT revealed a pooled overall response rate (ORR) of 95%,a CR rate of 80%, and a relapse rate of 19%.…”
Section: Vuković V Et Al Primary Central Nervous System Lymphomamentioning
confidence: 94%
See 2 more Smart Citations
“…Long-term follow-up of randomized phase 2 PRECIS study demonstrated advantage in 8-y event-free survival in ASCT arm over WBRT with 40 Gy (67% and 39%, respectively, p = 0.03), but without OS benefit (69% and 65%, respectively). Conversely, a significant deterioration in balances (52% vs. 10%, P ≤ 0.001) and neurocognition (64% vs. 13%, P < .001) was observed in WBRT over ASCT arm, suggesting avoidance of 40 Gy WBRT in consolidation within the first line treatment [35]. A systematic review and meta-analysis of 13 prospective trials encompassing 348 PCNSL patients treated with ASCT revealed a pooled overall response rate (ORR) of 95%,a CR rate of 80%, and a relapse rate of 19%.…”
Section: Vuković V Et Al Primary Central Nervous System Lymphomamentioning
confidence: 94%
“…First-line treatment regimens in PCNSL (adapted from Schaff et al, Blood 2021)(10,35) Tabela 2. Protokoli u prvoj liniji terapije u PCNSL (adaptirano iz Schaff et al, Blood 2021)(10,35) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with whole-brain radiation therapy (WBRT) there is reduced neurotoxicity in the long-term in patients with PCNSL. 57 A dynamic review of a patient’s performance status and overall fitness is recommended to assess transplant eligibility accurately as this may improve significantly after treatment initiation. Four phase II prospective trials support this approach in both treatment-naïve SCNSL and relapsed presentations ( Table 4 ).…”
Section: Treatment Approach For Secondary Central Nervous System Lymp...mentioning
confidence: 99%
“…In the companion to this article, 23 long-term outcomes and toxicity data of the PRECIS study are provided, with a median follow-up of 8 years, the longest follow-up to date of the survival and delayed toxicities of any cohort of patients with PCNSL prospectively treated with dose-intensive chemotherapy consolidation in comparison with WBRT (Table 1 A key question in comparing the IELSG-32 and PRECIS studies is as follows: why was there improved survival with ASCT compared with WBRT in the PRECIS study but not in the IELSG32 trial? One potential explanation is that the quality and depth of response to induction might have been significantly different between the two studies.…”
Section: Consolidation Strategies In Pcnslmentioning
confidence: 99%